2017
DOI: 10.3389/fnut.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

The Nutraceutic Silybin Counteracts Excess Lipid Accumulation and Ongoing Oxidative Stress in an In Vitro Model of Non-Alcoholic Fatty Liver Disease Progression

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a major cause of liver-related morbidity and mortality. Oxidative stress and release of pro-inflammatory cytokines, such as tumor necrosis factor α (TNFα), are major consequences of hepatic lipid overload, which can contribute to progression of NAFLD to non-alcoholic steatohepatitis (NASH). Also, mitochondria are involved in the NAFLD pathogenesis for their role in hepatic lipid metabolism. Definitive treatments for NAFLD/NASH are lacking so far. Silybin, the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 60 publications
3
32
0
1
Order By: Relevance
“…Several damages were observed at a mitochondrial level and elsewhere in the hepatocyte (reduced hepatocyte viability, increased apoptosis and oxidative stress, reduction in lipid droplet size, and up-regulation of I-κB kinase-interacting protein and adipose triglyceride lipase expressions). Notably silybin, the extract of the milk thistle seeds counteracted the FA-induced mitochondrial damage, increased the mitochondrial size and improved the mitochondrial cristae organization; stimulated mitochondrial FA oxidation; reduced basal and maximal respiration and ATP production in steatohepatitis hepatocytes; stimulated ATP production in steatotic cells, and rescued the FA-induced apoptotic signals and oxidative stress in steatohepatitis hepatocytes (Vecchione et al, 2017). In steatotic livers, ROS formation is increased at the mitochondrial respiratory chain level and determines oxidation of unsaturated lipids (Grattagliano et al, 2008;Grattagliano et al, 2003;Yang et al, 2000).…”
Section: Lipids Mitochondria and Agingmentioning
confidence: 99%
“…Several damages were observed at a mitochondrial level and elsewhere in the hepatocyte (reduced hepatocyte viability, increased apoptosis and oxidative stress, reduction in lipid droplet size, and up-regulation of I-κB kinase-interacting protein and adipose triglyceride lipase expressions). Notably silybin, the extract of the milk thistle seeds counteracted the FA-induced mitochondrial damage, increased the mitochondrial size and improved the mitochondrial cristae organization; stimulated mitochondrial FA oxidation; reduced basal and maximal respiration and ATP production in steatohepatitis hepatocytes; stimulated ATP production in steatotic cells, and rescued the FA-induced apoptotic signals and oxidative stress in steatohepatitis hepatocytes (Vecchione et al, 2017). In steatotic livers, ROS formation is increased at the mitochondrial respiratory chain level and determines oxidation of unsaturated lipids (Grattagliano et al, 2008;Grattagliano et al, 2003;Yang et al, 2000).…”
Section: Lipids Mitochondria and Agingmentioning
confidence: 99%
“…For instance, baicalin, a flavonoid obtained from Scutellaria baicalensis Georgi, has been demonstrated to have significant anti-inflammatory and antibacterial properties (7). In addition, several studies have reported that the flavonoid silybin reduced lipid accumulation and oxidative stress in vivo and in vitro (8,9). However, to the best of our knowledge, there are no previous studies that have evaluated the effects of Nob on lipotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Solanum melongena extract [46] Ganoderma lucidum [47] α-Arbutin [51] Auraptene [54] Oxidative stress Solanum melongena extract [46] Linalool [48] α-Arbutin [51] Naringenin [52] Apigenin [53] Auraptene [54] Apoptosis Ganoderma lucidum [47] Cinnamic acid derivatives [49] Proanthocyanidins [50] Naringenin [52] Apigenin [53] Naringenin [55] Ulmoside A [56] Mitochondrial membrane potential imbalance [59] Polygonatum kingianum [61] Betaine [63] Nicotinamide riboside [64] Puerarin [65] Punica granatum L. [62] Silybin [67] Salvianolic acid B [68] Oxidative stress Cimicifuga racemosa extract [59] Sipjeondaebo-tang [60] Polygonatum kingianum [61] 11 Oxidative Medicine and Cellular Longevity…”
Section: Energy Metabolism Obstructionmentioning
confidence: 99%
“…Nicotinamide riboside [64] Diosgenin [66] Silybin [67] NecroX-7 [69] Apoptosis Cimicifuga racemosa extract [59] Polygonatum kingianum [61] Betaine [63] Silybin [67] Salvianolic acid B [68] Mitochondrial membrane potential imbalance Cimicifuga racemosa extract [59] Sipjeondaebo-tang [60] Diosgenin [66] Salvianolic acid B [68] NecroX-7 [69] Fatty acid oxidation Silybin [67] NecroX-7 [69] T2DM…”
Section: Diseasesmentioning
confidence: 99%